(untitled) - Thomas, B. J. (London, 1977)
This book, for immediate and above EFL students, has 30 units, each of which consists of an extract from every day informational literature on some aspect of British daily life, followed by comprehension and composition exercises
Keywords: English language,English language; Composition and exercises